Type and Concentration Effects of some Active Ingredients on the Performance of Bentonite Lubricant Grease - Alghani, Mohammad Jamil Abd-; Sherhan, Bashir Yousif (Sulaimani Journal for Pure and Applied Sciences, 2014)
Optimization study was carried out on the materials used in preparation of lubricant grease prepared from bentonite. This study included the selection of the optimum type and percent of quaternary ammonium salts to convert the bentonite from hydrophilic to organophilic; tetraethyl ammonium chloride and tetraethyl ammonium bromide were used for this purpose. It was seen that the quaternary ammonium chloride gave the best results because of the high tendency of calcium ion to react with chloride ion than that with bromide ion; over more it gave a less swelling. The effect of treated bentonite added in different percentage on the penetration point, NLGI (National Lubricating Greases Institute number), drop point, and water resistance of the prepared grease was studied. It was seen that by increasing the percentage of added organophilic bentonite with the prepared grease caused a decrease in the penetration point which is correspond to increase in the consistency of stiffness of grease. These results were in agreement with the NLGI classification system. It was noticed that by increasing the percentage of added organophilic bentonite in the prepared grease caused an increase in the dropping point and in the degree of water resistance.
Keywords: Bentonite; NLGI; Grease Washout